Tantangan Etika dalam Jurnalisme Digital: Studi Kasus Peran Media Sosial dalam Penyebaran Berita - Triwulan, Dewi; Ramadhani, Nurabni; Zannah, Nurul; Naibaho, Melisa; Effendi, Erwan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to describe the ethical challenges of digital journalism, regarding the role of social media in news dissemination. This research is a qualitative descriptive study. The research results show that the ethical challenges of digital journalism can be seen from the development of media for reporting, starting from print media, mass media, and the current era of digital media where everyone can easily access information (reporting) from various social media today. The ethics of digital journalism can be seen from the non objective reporting that online journalism conveys news instantly and superficially. In fact, this challenge is the news that is conveyed now, it is difficult to know the facts of the news that is uploaded on various social media. One of them is fake news (hoax) which occurs due to a lack of reporting accuracy and journalists' instantaneousness in conveying news/information. The issue of accuracy is now a dilemma for online media which is pursuing speed in publishing information in real time, demanding it be fast but at the same time demanding it be accurate. These many demands often give rise to new problems. Not a few online media take shortcuts, namely by prioritizing speed over accuracy. The practice of self-plagiarism is widespread by repeating sentences in previous reports to recycle them as if they were new news. In certain cases, real-time online media began to emerge which reported quickly on an event, even though he and his team never went to the field to collect the news. Then create news titles or information that are clickbait (excessive titles or titles that sometimes do not match the existing news). These are the challenges faced by journalists in the advancement of technology and social media, sometimes resulting in news producers or readers consuming practical news that lacks accuracy.